BUILD SAFE SECURITY SYSTEMS USING CODE, FINGER PRINTS, AND CAMERAS WITH KANSEI ENGINEERING METHOD - Hary Nurdi; Adi Bandono; I Made Jiwa Astika (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2021)
The Financial Office of Koarmada II (Disku Koarmada II) has the ability to support the KRI oprasional or unit that is the demand of the Navy. To support the implementation of these tasks, the Koarmada II Financial Office needs to be equipped with special equipment to support the implementation of tasks in storing money and valuable state assets. IoT safe security system. That will monitor the security conditions in a storage is certainly very necessary for financial holders to be able to monitor the security conditions in the safe even remotely. Currently, The Financial Office of Koarmada II does not have a security system in the safe, in this study the author tried to design a security system with the Internet of things system, from the results of research on the entire system that works smoothly and the process of sending reports on accessing the safe to the mobile phone is very good. With this system, it is expected that financial holders can monitor through the application on the mobile phone if anyone accesses the safe, so as to prevent before the breach of the safe, even know if there are people who try to access the safe. From the existence of this security system will be able to complete the main tasks effectively and efficiently and able to minimize material losses. Keywords : Kansei Engineering, Security Safe IoT system